Expression and association of miR-181a and miR-663 and their target genes in head and neck cancer - Masood, Yaghma (2018)
Head and neck cancer is the sixth most common malignancy worldwide and the fifth most common cancer in peninsular Malaysia. The over five-year survival rate for patients with HNC is only 40-50% because of distant metastasis, loco-regional recurrences, and secondary primary tumours. miRNAs have been shown to be able to regulate many cellular processes, including proliferation, differentiation, angiogenesis, cell development, etc. There is strong evidence that miRNAs may represent different targets for anticancer therapies. The aberrant expression of human microRNA-181a-2- 3p and miR-663 has been implicated in the pathogenesis of various cancers. However, the role of hsa-miR-181a-2-3p and hsa-miR-663 in the pathogenesis of head and neck cancer and its clinical significance are still unclear. This study is the continuation of previous work done by our research group where novel expression of hsa-miR-181a-2-3p was found in head and neck cancer. To check and compare the expression of hsa-miR-181a-2-3p, hsa-miR-663 was selected, which already has established expression in HNC. Therefore, the aim of this study was to search for the molecular targets of hsa-miR-181a -2-3p and hsa-miR-663 and determine their expression and their common predicted targets in HNC. So, it was hypothesised that hsamiR- 181a-2-3p and hsa-miR-663 may play an important role in the progression of head and neck cancer and co-regulate few common targets which lead to the activation of cancer pathways in HNC development. To predict the targets of hsa-miR-181a -2-3p and hsa-miR-663, three different algorithms were used, including TargetScan, miRanda-mirSVR and RNA22 HAS. Two algorithms, TarBase and miRTarBase, were used to identify the validated targets of hsa-miR-181a-5p (a mature product of hsa-miR-181a) and hsa-miR-663. To further narrow down the list of targets identified from the in silico analysis, the target genes of hsa-miR-181a-2-3p and hsa-miR- 663 were further validated by published literature, before using them in this research project. The web-based Database for Annotation, Visualization and Integrated Discovery tool (DAVID) was used to provide biological functional interpretation of the validated targets of hsa-miR-181a-5p and hsa-miR-663. A total of 70 formalin-fixed paraffin embedded (FFPE) tissue specimens and 4 fresh frozen (FF) tissue samples from HNC patients (26 stage I,15 stage II, 11 stage II and 22 stage IV HNC cases), and 12 non-cancerous FF samples were collected from the Peninsular Malaysian population. The expression of these miRNAs and their common predicted targets were determined by doing q-PCR in HNC cell line, non-cancerous samples and HNC samples. Bioinformatic studies have showed that hsa-miR-181a and hsa-miR-663 might regulate a large number of target genes that are important in the regulation of critical cell processes, such as cell fate, cell survival, metabolism, and cell death. To date, 584 targets of hsa-miR-181a have been validated; and 61 of these targets are cancer genes. In addition, it was identified that 101 targets of hsa-miR-663 have been validated; and 15 of these targets are cancer genes. The precision of predictions by all the algorithms for hsa-miR-181a-2-3p and hsa-miR-663 targets was low. Based on the DAVID and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, it is concluded that many of these genes are involved in tumorigenesis of various cancers, including HNC. Besides this, the main cancer pathways regulated by hsa-miR-181a and hsa-miR-663 could be PI3K/Akt, MAPK, and Wnt signaling pathways in head and neck cancer. Based on the amalgamation of in silico analysis and published literature, nine common predicted targets (ATM, BCL2, BCL2L2, CDKN1A, CDKN1B, DDIT4, p53, p73 and PARP1) of hsa-miR-181a-2-3p and hsa-miR-663 were chosen for further experimental investigation. Moreover, results in this study showed that advanced HNC had a significant higher expression level of hsamiR- 181a-2-3p and hsa-miR-663 than that in early stage of HNC, suggesting that it may have a critical role in tumor metastasis of advanced HNC. It was also found that BCL2 and PARP1 were also upregulated along with upregulation of hsa-miR-181a-2-3p and hsa-miR-663 in HNC compared to that in non-cancerous tissues. However, ATM, CDKN1A, CDKN1B, DDIT4, p53 and p73 expression were inversely correlated with hsa-miR-181a-2-3p and hsa-miR-663 expression. Taken together, these results suggest that hsa-miR-181a-2-3p and hsa-miR- 663 may serve as an oncogene in head and neck cancer. Furthermore, hsamiR- 181a-2-3p and hsa-miR-663 might be used as new biomarkers together with their common predicted targets in the prediction of prognosis of HNC in clinical practice. More functional and mechanistic studies are needed to validate the role of hsa-miR-181a-2-3p and hsa-miR-663 in the development, progression, and metastasis of HNC.